Skill development in experimental courses - Héctor Bagán; Rosa Sayós; José Francisco García (OmniaScience, 2015)
Experimental courses offer a good opportunity to work with competences, promoting the incorporation of strategies oriented towards motivating students to actively involve in the learning process, promoting reflexive learning and developing generic skills. This study presents different ways of developing and evaluating some important general skills, settle on four specific objectives: 1. To increase student motivation using samples of potential interest to students and explaining real-live application of their samples analyses; 2. To assist students' self-regulation and learning autonomy by using the portfolio; 3. To promote group work through experiments in pairs and small-group discussions; 4. To develop communication skills through small-group discussions and oral presentations. Results show that the type of sample used and real-life application has important influence on motivation. The portfolio is a good tool to promote reflection and to evaluate both specific and generic skills in experimental courses, the dynamics of a laboratory course permit students to develop their group-work and communicative skills, and peer evaluations both improve students' communication skills and promote metacognitive reflection. Finally, the project demonstrates that it is possible to train students in general skills using the specific course content and that the incorporation of participatory methodologies encourages students to become actively involved in the teaching-learning process.